Reusable Learning Objects: Tools for Teaching in Nonformal Education - Jessica L. Gouldthorpe; Amy Harder; T. Grady Roberts; Nicole Stedman (EDIS)
Reusable learning objects are short, self-contained, digital learning activities that can be valuable tools for sharing information. This 4-page fact sheet provides a brief synopsis of what reusable learning objects are and how to create them for use in an educational setting. Written by Jessica L. Gouldthorpe, Amy Harder, T. Grady Roberts, and Nicole Stedman, and published by the UF Department of Agricultural Education and Communication, April 2013.